“Defensa de Proyectos de Investigación de la Carrera de Ingeniería en Administración para Desastres y Gestión del Riesgo” - Llivi Ruilova, Danny Vicente (2023)
To obtain their professional degree, students of the Engineering in Disaster Administration and Risk Management degree at the UEB defended their research projects; complying with the schedule established by Eng. Luis Villacis, coordinator of the Titling Unit.